Characterization of Protein Hydrolysate from Dog Conch (Strombus sp) Using Bromelain Enzyme - Rahman, R Fathul; Mannullang, Benny; Prastari, Cindyta; Seulalae, Anggrei Viona (Universitas Teuku Umar, 2025)
This study was conducted to determine the chemical characteristics of the dog conch protein hydrolyzate (Strombus sp). The research method consists of 2 stages, namely 1) preparation of dog conch flour and chemical composition analysis and 2) making dog conch protein hydrolyzate using 2% bromelain enzyme and chemical composition analysis. The flour parameters observed were water content, ash, protein, fat, and yield. Meanwhile, the protein hydrolyzate composition parameters observed were the degree of hydrolysis, dissolved protein, and amino acids. The research results show that the chemical composition of dog conch flour is water content 9.30% (ww), ash content 7.09% (dw), protein content 73.42% (dw), fat content 7.54% (dw), and the yield of dog conch flour is 87.5%. Meanwhile, the chemical composition of the dog conch protein hydrolyzate is 78.5% degree of hydrolysis, 69% soluble protein, and 27.998% total amino acids.